2017
DOI: 10.1016/j.biomaterials.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Micro-fabricated scaffolds lead to efficient remission of diabetes in mice

Abstract: Despite the clinical success of intrahepatic islet transplantation in treating type 1 diabetes, factors specific to this transplantation site hinder long-term insulin independence. The adoption of alternative, extravascular sites likely improve islet survival and function, but few locations are able to sufficiently confine islets in order to facilitate engraftment. This work describes a porous microwell scaffold with a well-defined pore size and spacing designed to guarantee islet retention at an extrahepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…The small pores will help promote blood vessel ingrowth into the bioscaffold, as supported by recent reports which have shown that pore sizes between 30–40 mm facilitates vascularization of implantable bioscaf-folds. 50,51 Our bioscaffold also has a high degree of porosity (75% ± 3%) with a corresponding high swelling ratio. 48 The high porosity and interconnected macropores of our bioscaf-fold creates a physical space to facilitate cell movement and distribution throughout the bioscaffold.…”
Section: Discussionmentioning
confidence: 90%
“…The small pores will help promote blood vessel ingrowth into the bioscaffold, as supported by recent reports which have shown that pore sizes between 30–40 mm facilitates vascularization of implantable bioscaf-folds. 50,51 Our bioscaffold also has a high degree of porosity (75% ± 3%) with a corresponding high swelling ratio. 48 The high porosity and interconnected macropores of our bioscaf-fold creates a physical space to facilitate cell movement and distribution throughout the bioscaffold.…”
Section: Discussionmentioning
confidence: 90%
“…Chen et al, 2007). Islets transplanted into the epididymal fat produced similar results to islets transplanted intraportally, although encapsulation or tissueengineered strategies are required (Buitinga et al, 2017;Manzoli et al, 2017;D. Mao et al, 2017;Rios, Zhang, Luo, & Shea, 2016; K. Wang, Wang, Han, Chen, & Luo, 2017;X.…”
Section: (D)mentioning
confidence: 93%
“…Like the omentum , it is easily accessible and well vascularized, although it does not have portal drainage (X. Chen et al, ). Islets transplanted into the epididymal fat produced similar results to islets transplanted intraportally, although encapsulation or tissue‐engineered strategies are required (Buitinga et al, ; Manzoli et al, ; D. Mao et al, ; Rios, Zhang, Luo, & Shea, ; K. Wang, Wang, Han, Chen, & Luo, ; X. Wang, Wang, Zhang, Qiang, & Luo, ; Weaver et al, ). The renal subcapsular space has been considered one of the best sites for islet transplantation for more than 3 decades (Mellgren, Schnell Landström, Petersson, & Andersson, ) and is used as a positive control in most studies instead of the liver (Ar’Rajab, Ahrén, Alumets, Lögdberg, & Bengmark, ; Halberstadt et al, ; Medarova et al, ; Pepper et al, ). Compared to intraportally transplanted islets, renal subcapsular islet grafts show a faster vascular engraftment that increases success rates (Olsson, Olerud, Pettersson, & Carlsson, ; Stokes et al, ).…”
Section: The Liver As a Suboptimal Receptor Site For Islet Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…Although majority of biotechnology research related to islet transplantation has focused on encapsulation strategies,1–3 there has been a growing interest in creating new biocompatible 3D structures, known as bioscaffolds 4–8. Bioscaffolds provide an interesting solution for islet transplantation given that they contain spaces that can accommodate islets while concurrently offering a unique interface which can be modulated to address critical shortcomings faced by islets in the immediate post‐transplantation period (i.e., hypoxia) 9.…”
Section: Introductionmentioning
confidence: 99%